Biodegradable poly(D,L-lactic-co-glycolic acid)-based micro/nanoparticles for sustained release of protein drugs - a review - Ansary , Rezaul H.; Awang, Mohamed Bin; Rahman, Md. Mokhlesur (Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, 2014)
Biodegradable poly(D, L-lactide-co-glycolide) (PLGA) and PLGA-based polymeric nanoparticles are widely used for sustained release of protein and peptide drugs. These formulations are usually prepared by water/oil/water (W/O/W) and solid/oil/water (S/O/W) double emulsion solvent evaporation method. Other methods of preparation are nanoprecipitation, emulsion solvent diffusion and salting-out. This review attempts to address the effects of PLGA molecular weight, lactide to glycolide ratio, crystallinity, hydrophilicity as well as nanoparticles preparation variables (e.g., homogenizer speed, surfactants nature and concentration) on the size, morphology, drug encapsulation efficiency and release profile of PLGA mico/nanoparticles. The current knowledge of protein instability during preparation, storage and release from PLGA micro/nanoparticles and protein stabilization approaches has also been discussed in this review.